Efficacy of Combinatorial Inhibition of Hedgehog and Autophagy Pathways on the Survival of AML Cell Lines - Sansacar, Merve; Pepe, Nihan Aktas; Akcok, Emel Basak Gencer; El Khatib, Mona; Gencer Akçok, Emel Başak (Academic Press inc Elsevier Science, 2025)
Acute myeloid leukemia (AML) is a common hematopoietic disease that results from diverse genetic abnormalities. Dysregulation of important signaling pathways, including the PI3K/AKT/mTOR, Wnt and Hedgehog pathways, plays crucial roles in the development of AML. Hedgehog pathway (Hh) is a conserved signaling pathway that is crucial throughout embryogenesis. Hh plays an important role in the regulation of autophagy, known as the cellular recycling process of organelles and unwanted proteins. Many studies have noted that the modulation of autophagy could act as a survival mechanism in AML. Considering the pivotal role of autophagy and Hh signaling in AML, understanding the relationship between these pathways is important for overcoming leukemia. Therefore, we examined the efficacy of Hh inhibition by GLI-ANTagonist 61 (GANT61) in MOLM-13 and CMK cells via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenil-2H-tetrazolium bromide (MTT) cell viability assays. GANT61 resulted in decreased cell viability in both cell lines. Therefore, we focused on the outcome of autophagy modulation in AML cells. We observed that the autophagy inhibitors ammonium chloride (NH4CI), chloroquine (CQ), and nocodazole led to a significant reduction in the proliferation of both cell lines. Cotreatment with autophagy pathway inhibitors and GANT61 synergistically affected both AML cell lines. Moreover, dual targeting of these pathways resulted in arrest at the G0/G1 phase in MOLM-13 cells but not in CMK cells. Furthermore, the combination of nocodazole and GANT61 increased the expression level of LC3B-II in both cell lines. Compared with that in the untreated control cells, the GLI1 gene expression level in both cell lines was significantly lower after GANT61 and autophagy cotreatment. In conclusion, targeting Hh and autophagy could be a favorable option to combat AML.
Keywords: Cancer; Leukemia; Autophagy; Hedgehog Pathway; Combination Therapy